We Have Sent Ourselves to Iceland (With Apologies to Iceland): Changing the Academy From Internally-Driven to Externally Partnered - Singh, Gerald G. (Frontiers in Sustainable Cities, 2022)
In Brave New World, Aldus Huxley presented a dystopic vision of the world where global despotic power was maintained, in part, through isolating academics in Iceland. Current academic accountability is based on notions of excellence that reflect prestige. In governing itself based on excellence, I argue academia has metaphorically sent itself to Iceland, which has consequences for the relevance of academia towards sustainable development. Internally-driven academies are facing their own sustainability issues, as more students are trained for too-few professor positions, and must find work in other fields with inadequate training. Academic measures of excellence attempt to reflect merit but perpetuate pre-conceived notions of prestige, which is discriminatory, contributes to intellectual gate-keeping, and distracts from research rigor and policy relevance. Measures of excellence fail to translate to real-world impact in three important ways: academic reviews that accounts for prestige lead to poor and biased predictions of outcomes of research projects; prestigious individuals are not more reliable experts than less prestigious individuals (and may be more overconfident); prestigious institutions are not more likely to contribute to sustainable development outcomes than less prestigious institutions. It is time to drop academic notions of excellence and turn towards external partnerships, where academic institutions can focus more on real-world impact, train students for diverse careers, and allow academic research to focus on quality over quantity. For academia to be relevant to society, and to serve people graduating academic institutions, academia must proactively leave Iceland and rejoin the rest of the world.